(untitled) (Medico Legal Update, 2021)
Before marriage, couples are screened through a procedure known as premarital screening for different genetic, infectious or bloodborne diseases that can be passed from them to their offspring. The aim of our research was to assessment the premarital screening of couples for hemoglobinopathies and undiagnosed cases with suggestive findings of thalassemia or its variants. and evaluation hematology parameters among common Hb hemoglobinopathy. This study contains 228 individuals with hemoglobinopathy, the participants were couples attending primary health centers for regular premarital inquiries in baquba teaching hospitals, Iraq. ?-thalassemia was enrolled in 3 (1.3%) from all hemoglobinopathy individuals, ?-thalassemia was enrolled in 255 (98.8 %), which include ?-thalassemia minor in 226 individuals 88.6%, while ? thalassemia intermediate in 5 individuals 2.2% from all individuals with hemoglobinopathy Figure 1 and 2. Others thalassemia was recorded 3 Hb-E 1.1%, 1 Hb-S 0.39, 10 Hb-D 3.92, 13Hb-C 5.09. Pre-marital examinations are important to determine hemoglobinopathy and limit transmission to offspring, as well as blood tests are important to identify people with haemoglobinopathy and its influence.